Hazardous Waste Management By TSDF - Kumari, Supriya (My University, 2016)
The study describes the overall view and the facilities available at the TSDF site as well as the detailed TSDF operating procedures were discussed starting from receiving of the hazardous waste from the generator to the final disposal into the landfill. In this study several different samples of hazardous waste were collected and analysed. Both Comprehensive and finger print analysis were performed for each sample. From the Comprehensive analysis, the characterization of waste was determined which decides the flow pathways of waste that whether it is sent for direct landfill, landfill after treatment or incineration. Multiple trials of Reciepe development was conducted for the ‘landfill after treatment’ method and the best reciepe having all contaminant parameters lying within the permissible limit was chosen for stabilization.
M.Tech (Environmental Science and Technology) Dissertation
Keywords: treatment; storage; disposal; facility; hazardous waste